The thrombocyte aggregation process in the turtle Phrynopys hilarii (Chelonia). An ultrastructural study - Pellizzon, C. H. [UNESP]; Azevedo, A. [UNESP]; Casaletti, L.; Lunardi, L. O. (My University, 2002)
This study investigates the thrombocyte aggregation process in the South American fresh water turtle (Phrynopys hilarii) using electron microscopy. Blood was taken from surgically exposed lateral neck vessels often turtles Phrynopys hilarii during the spring and summer seasons, when the mean temperature is 37°C. Blood samples were fixed with Karnovsky solution for processing by transmission electron microscopy. The turtle thrombocytes were spindle-shaped with lobulated nuclei. Prominent vesicles and canaliculi were found throughout the cytoplasm. The cytoplasm organelles showed an agranular endoplasmatic reticulum, Golgi complex near the centrioles and scattered free ribosomes. These cells are similar to bird thrombocytes but distinct from fish and frog thrombocytes. Blood clotting time was 5 min ± 30 sec measured by the Lee and White method. Structural alterations resulting from the aggregation process occurred after activation. Thrombocytes developed numerous filopodial projections, an increased number of vacuoles and changed from spindle to spherical shape. P. hilarii thrombocytes have different morphologic characteristics compared to other non-mammalian vertebrate cells. These cells can participate in the aggregation process, as observed in birds.
Keywords: Aggregation; Morphology; animal cell; bird; blood clotting; blood sampling; cell activity; cell aggregation; cell granule; cell organelle; cell shape; cell ultrastructure; cell vacuole; controlled study; correlation analysis; electron microscopy; endoplasmic reticulum; exposure; fish; frog; micromorphology; nonhuman; nucleolus; phrynopys hilarii; ribosome; species comparison; spring; structure analysis; summer; temperature dependence; thrombocyte aggregation; transmission electron microscopy; turtle; animal; animal disease; blood clotting time; cell nucleus; cell surface; chemistry; cytoplasm; echography; immunohistochemistry; physiology; thrombocyte; ultrastructure; Animalia; Anura; Aves; Mammalia; Testudines; Vertebrata; serotonin; Animals; Blood Platelets; Cell Nucleus; Cell Surface Extensions; Cytoplasm; Immunohistochemistry; Microscopy, Electron; Platelet Aggregation; Serotonin; Turtles; Whole Blood Coagulation Time